The Challenges of Hypertext Reading Comprehension for Adults: A Literature Review (Revista de Psicología, 2024)
The aim of the article is to discuss the most relevant contributions of the last decade in relation to reading comprehension for hypertext format, in the adult population without reading difficulties and in their mother tongue. Some studies suggest the existence of negative effects in reading under hypertext conditions on reading comprehension. Other studies point out the importance of individual cognitive differences as moderating and mediating variables in these effects, including the level of working memory and the reader's prior knowledge. On the other hand, some studies indicate possible moderating external variables such as the use of navigation aids (that is, the use of hyperlinks and instructions to facilitate the reading task and underlining).
Keywords: Hypertext; Reading comprehension; adult people